Management of Orobanche in mustard crop through glyphosate application - Punia, S. S.; Duhon, Anil; Sharma, A. R. (Indian Farming, 2018)
To avoid any possible toxic or suppressive effect of glyphosate even at the recommended low dose on mustard plants, it is advisable to ensure that the crop does not suffer from moisture stress at the herbicide spray. Therefore, irrigation may be applied 2-3 days prior to or 1-2 days after the herbicide application.